Hedonic modeling of estimated progeny differences in angus bull sale auctions - Melchor, Matthew Miguel (Kansas State University, 2024)
Seedstock consumers each value estimated progeny difference values in their own unique way, emphasizing certain traits they believe estimate the best possible genetic makeup over others. Some producers still do not believe they hold much, if any, merit, due to the recency of these standardized measurements. These measurements were created to compare animals within the same breed, and now across different breeds, to each other for desirable traits to cow-calf producers. This analysis utilizes data from the Kansas State University Department of Animal Sciences and Industry’s annual Legacy Bull Sale and Vollmer Angus Ranch in North Dakota to estimate the economic effects certain EPDs have on the price a bull sells for at each sale. Data was gathered for the Legacy Sale from the years 2016-2023, yielding 128 observations and 22 independent variables, and Vollmer Angus Ranch from 2019-2023, yielding 556 observations and 13 independent variables. The datasets were analyzed for each sale for their given years, a combined time-series dataset of the two sales from 2019-2023, and then combined annually to assess certain variables that were only calculated for a certain year. A hedonic model was used to investigate statistically significant variables and a correlation matrix was assessed to reduce or eliminate correlated independent variables. The results show that producers value different EPDs across the Legacy and Vollmer Angus Ranch sales, as well as different emphasis on certain variables across years. Although this model demonstrates producers are willing to pay more for certain traits, a larger sample size including more university sales or private auctions could give a more accurate representation of the overall seedstock industry’s targeted traits and how they affect price. Including other industry data, gathered either through the American Angus Association, auction sites, or the hosts themselves, can better estimate the comparison between the two separate types of bull sales.
Keywords: Estimated progeny difference; Livestock genetics